2018
DOI: 10.1007/s11047-018-9696-8
|View full text |Cite
|
Sign up to set email alerts
|

A survey of cellular automata: types, dynamics, non-uniformity and applications

Abstract: Cellular automata (CAs) are dynamical systems which exhibit complex global behavior from simple local interaction and computation. Since the inception of cellular automaton (CA) by von Neumann in 1950s, it has attracted the attention of several researchers over various backgrounds and fields for modelling different physical, natural as well as reallife phenomena. Classically, CAs are uniform. However, non-uniformity has also been introduced in update pattern, lattice structure, neighborhood dependency and loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 276 publications
(334 reference statements)
0
31
0
1
Order By: Relevance
“…Hücresel otomatlar ilk olarak biyolojik ve fiziksel sistemlerin modellenmesinde kullanıldı. 1980'lerden sonra gerçek hayat problemleri üzerinde kullanılmaya başlamıştır [22].…”
Section: Yöntemle İlgili çAlışmalar (Methods Related Work)unclassified
“…Hücresel otomatlar ilk olarak biyolojik ve fiziksel sistemlerin modellenmesinde kullanıldı. 1980'lerden sonra gerçek hayat problemleri üzerinde kullanılmaya başlamıştır [22].…”
Section: Yöntemle İlgili çAlışmalar (Methods Related Work)unclassified
“…Another interesting aspect of using cellular automata is that both uniformity and non-uniformity can be modeled. A cellular automaton is defined as [3] (d, L, S, N, f ), where d represents the cellular space dimension, L represents the cellular space, S is the finite set of states, N is the neighborhood vector and f or (f 1 ,f 2 ,...) is the local rule or ruleset respectively. The global rule of the cellular automata is designated by Φ.…”
Section: Background On Cellular Automatamentioning
confidence: 99%
“…CAs are widely used in cryptography and other fields to benefit from their simplicity, parallelism, and unpredictability. Besides, CAs make the hardware and software implementations easier [3]. In this paper, a new design called CA-PCS (Cellular Automata based Partition Ciphering System) is proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Though the precise mechanism of how computation is derived from propagation is unknown, one possibility is that it is the result of what one might consider to be 'information collisions.' This idea is based on the finding of Lizier et al (2010) who demonstrated that the dominant form of information modification (i.e., computation) in cellular automata are the result of collisions between the emergent particles (see also Adamatzky and Durand-Lose, 2012;Bhattacharjee et al, 2016;Sarkar, 2000). In the context of our circuits, the idea is that computation arises when packets of information embedded in the outgoing spike trains of sending neurons collide onto the same receiving neuron in sufficient temporal proximity to alter the way the receiver responds to those inputs.…”
Section: Rich Clubs As a Home For Computationmentioning
confidence: 99%